Development of Different Methods for Preparing Acinetobacter baumannii Outer Membrane Vesicles Vaccine: Impact of Preparation Method on Protective Efficacy - Li, Sun; Chen, Da-Qun; Ji, Lu; Sun, Si; Jin, Zhe; Jin, Zi-Li; Sun, Hong-Wu; Zeng, Hao; Zhang, Wei-Jun; Lu, Dong-Shui; Luo, Ping; Zhao, An-Ni; et al. (Frontiers in Immunology, 2020)
Acinetobacter baumannii (A. baumannii) is becoming a common global concern due to the emergence of multi-drug or pan-drug resistant strains. There is a growing appreciation for the strategy to confront the problem of antimicrobial resistance by developing vaccines against the resistant pathogen. In this study, different methods for preparing A. baumannii outer membrane vesicles (AbOMVs) vaccine were developed. sOMV (spontaneously released AbOMV) was extracted from the culture supernatant, while SuOMV (sucrose-extracted AbOMV) and nOMV (native AbOMV) were prepared from the bacterial cells. Three AbOMVs exhibited significant differences in yield, particle size, protein composition and LPS/DNA content. To compare the protective efficacy of the three AbOMVs, groups of mice were immunized either intramuscularly or intranasally with each AbOMV. Vaccination via both routes conferred significant protection against lethal and sub-lethal A. baumannii challenge. Moreover, intranasal vaccination provided more robust protection, which may be attributed to the induction of significant sIgA response in mucosal sites. Among the three AbOMVs, SuOMV elicited the highest level of protective immunity against A. baumannii infection whether intramuscular or intranasal immunization, which was characterized by the expression of most profound specific serum IgG or mucosal sIgA. Taken together, preparation method had a significant effect on the yield, morphology and composition of AbOMVs, then further influenced the protective effect against A. baumannii infection.